(untitled) (Research, Society and Development, 2026)
Contemporary medical education demands active methodologies capable of integrating theory and practice in real care settings, especially in the context of Primary Health Care. The critical-reflective portfolio stands out as a pedagogical tool that fosters critical thinking and promotes integration between teaching, health services, and community. The aim of this study was to report the experience of using a critical-reflective portfolio as a strategy for integrating teaching, service, and community in medical education. This is an experience report of a descriptive nature with a qualitative approach, developed between May and August 2025 in a Family Health Unit in Altamira, Pará, Brazil, involving medical students in supervised practical activities. The use of the portfolio enabled the integration of theory and practice, facilitated the identification of social determinants of health, expanded clinical reasoning, and contributed to the development of communication skills and a humanized approach. It also encouraged critical reflection on ethical dilemmas and patient-centered care. Challenges included high academic workload and the lack of structured evaluative criteria. It is concluded that the critical-reflective portfolio is a relevant strategy for medical education, promoting integration between teaching, service, and community and contributing to the development of clinical, ethical, and social competencies.